2023
DOI: 10.1177/10815589221140597
|View full text |Cite
|
Sign up to set email alerts
|

Anemia prevalence time trends and disparities in the US population: examination of NHANES 1999–2020

Abstract: While a rising prevalence of anemia in the United States was reported in older studies, recent data are lacking. To estimate the prevalence and time trends of anemia in the United States and to examine how these estimates differ by gender, age, race, and household income to poverty threshold ratio (HIPR), we used the National Health and Nutrition Examination Surveys from 1999 to 2020. The presence of anemia was determined using the World Health Organization criteria. Survey-weighted raw and adjusted prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
(26 reference statements)
0
7
1
Order By: Relevance
“…This is all worth exploring in depth in future studies. Besides, hospitalizations for nutritional anemia in the United States are a gradual decline from 2016 to 2020, which is slightly different from the previous studies ( 13 , 17 ). This decline could be attributed to the implementation of health policies and healthcare reforms in the previous years, alongside ongoing advancements in medical care and improving economic conditions.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…This is all worth exploring in depth in future studies. Besides, hospitalizations for nutritional anemia in the United States are a gradual decline from 2016 to 2020, which is slightly different from the previous studies ( 13 , 17 ). This decline could be attributed to the implementation of health policies and healthcare reforms in the previous years, alongside ongoing advancements in medical care and improving economic conditions.…”
Section: Discussioncontrasting
confidence: 85%
“…In 2021, anemia affected approximately 24.3% of the global population across all age groups with totaling 1.92 billion cases, contrasting with rates of 28.2% and 1.50 billion cases recorded in 1990 ( 12 ). Although the United States has a lower incidence of anemia compared to the global average, a previous research based on the National Health and Nutrition Examination Survey (NHANES) database indicated an almost doubling of cases, rising from 4.03% in 1999 to 6.49% in 2020 ( 13 ). Other studies ( 14 , 15 ) have also shown that the prevalence of anemia in the U.S. has been increasing every year for the last 20 years, which serves as a warning highlighting the need to pay greater attention to anemia.…”
Section: Introductionmentioning
confidence: 99%
“…However, iron supplementation results in lower depression and stress in previously iron‐deficient mothers (Azami et al, 2019). Hwang et al (2023) reported that the anemia prevalence in the United States is higher for African Americans and Hispanics compared to the majority. Postpartum anemia can cause cognitive difficulties (e.g., concentration, recall, problem solving), emotional instability, and depression, placing postpartum women at elevated PPD risk (Ferreira et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, iron supplementation results in lower depression and stress in previously iron-deficient mothers (Azami et al, 2019). Hwang et al (2023) reported that the anemia prevalence in the United States is higher for African Americans and Hispanics compared to the majority.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of anemia in the United States increased from 4.03% to 6.49% between 1999 and 2020. 7 Anemia affects both physical health and mental health, resulting in decreased physical functioning and neuropsychological development, 8 , 9 as well as fatigue and emotional/psychological problems. 10 Anemia might also induce changes in the hippocampus, corpus striatum, and monoamine levels that lead to mental disorders, 11 increasing the risk of mental health.…”
Section: Introductionmentioning
confidence: 99%